ANALISIS MONITORING UNTUK PENCEGAHAN AKSES ILEGAL DI DALAM JARINGAN DEPARTEMENT TI PT. PUSRI - Ariyadi, Tamsir; Ikrar Agamuri, M.Alzi; Wiratama, Rahmat; Kholid, Dasril (JURNAL ILMIAH INFORMATIKA, 2025)
Technology plays an important role in human survival in daily activities that cannot be separated from technology. Information technology makes it easy for humans to share information or search for information. Cyber ​​attacks such as malware attacks or hacking attempts are a serious threat to IT networks. The purpose of network security is to anticipate the risk of network threats that can disrupt daily computer network operations. In this study, the author used the Action Research method. This study aims to test and develop, find and design. The network in the IT Department of PT. Pupuk Srwidjaja Palembang is quite safe because when network monitoring was carried out for 10 days on June 6, 2023 to June 22, 2023, there was no illegal access.